The European Food Safety Authority recommendation for polyunsaturated fatty acid composition of infant formula overrules breast milk, puts infants at risk, and should be revised. (December 2015) - Crawford, Michael A.; Wang, Yiqun; Forsyth, Stewart; Brenna, J. Thomas
Abstract: The European Food Safety Authority (EFSA) has concluded from a limited review of the literature that although docosahexaenoic acid (DHA) is required for infant formula, arachidonic acid is not required " even in the presence of DHA " (EFSA Journal, 12 (2014) 3760). This flawed opinion is grounded in human trials which tested functionality of DHA in neural outcomes and included arachidonic acid ostensibly to support growth. The EFSA report mistakes a nutrient ubiquitous in the diets of newborn infants, through breast milk and with wide-ranging health and neurodevelopmental effects, for an optional drug targeted to a particular outcome that is properly excluded when no benefit is found for that particular outcome. Arachidonic acid has very different biological functions compared to DHA, for example, arachidonic acid has unique functions in the vasculature and in specific aspects of immunity. Indeed, the overwhelming majority of trials include both DHA and arachidonic acid, and test development specific to DHA such as neural and visual development. DHA suppresses membrane arachidonic acid concentrations and its function. An infant formula with DHA and no arachidonic acid runs the risk of cardio and cerebrovascular morbidity and even mortality through suppression of the favorable oxylipin derivatives of arachidonic acid. The EFSA recommendation overruling breast milk composition should be revised forthwith, otherwise being unsafe, ungrounded in most of the evidence, and risking lifelong disability.